A post Keynesian perspective on twenty-first century economic problems - International Post Keynesian Workshop 2000 Knoxville, Tenn.)/ Davidson, Paul; International Post Keynesian Workshop 2000 : Knoxville, Tenn.); Davidson, Paul, 1930- (Northampton, MA : Edward Elgar Pub., 2002)
This book offers new policy prescriptions from the post keynesian perspective to achieve full employment without inflation.
Includes index.
aia 10/09/13
Loan
Keywords: Keynesian economics -- Congresses; Economic history -- Congresses